Hoạt tính xúc tác của Cu trong phản ứng phân hủy N2O - Minh Huệ, Nguyễn Thị; Tuấn, Nguyễn Minh; Mơ, Nguyễn Thị; Cầm, Lê Minh (Vietnam Journal of Chemistry, 2016)
The focus of the performed studies is Cu containing catalysts for nitrous oxide decomposition in the temperature range of 200÷600 oC. Catalytic samples have been synthesized by wet impregnation method. Prepared materials are characterized by means of XRD and N2 adsorption/desorption. The obtained results reveal that Cu or Fe supported catalysts, especially Cu (or Fe)/ZSM-5, exhibit very promising activity and they are good catalysts for decomposition of N2O. An optimal copper loading of 5 wt% is found. Further increase of Cu-loading to 7 % results in the formation of segregate and less active phase. Of the three supports, ZnO, Al2O3 and ZSM-5 used, H-ZSM-5 produces the most effective catalyst for N2O decomposition due to acid nature, high surface area and high order pore structure. The decomposition of N2O follows two stages. At low temperatures, N2O decomposes to N2 and surface oxygen atoms. The second high temperature stage involves the formation of O2 and the rate of oxygen formation correlates with catalytic activity. Fast desorption of O2 increases the number of effective sites and therefore the catalyst is regenerated. Keywords. Decomposition, N2O, copper, ZSM-5, Al2O3